The role, significance and challenges arising from the cooperation of technical universities and enterprises on a selected example of Polish polytechnics - Dylik, Justyna (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The purpose of this publication is to present the results of a proprietary study dedicated to exploring the topic of the importance of cooperation between technical universities in Poland and small and medium-sized enterprises, as well as the challenges arising from such cooperation. The phenomenon of cooperation is becoming more and more important nowadays, when the entry of Polish small and medium enterprises into the era of the digital economy is inevitable. Therefore, the importance of seeking new solutions and areas of cooperation increases, which is associated with new challenges faced by both environments. The study used the telephone interview method. There are many factors motivating cooperation, but the real challenge is to minimize significant restrictions affecting the development of such cooperation as well as creating conditions for mutual cooperation.